Smong: Kearifan Lokal Sebagai Bentuk Warisan Budaya Mitigasi Bencana Masyarakat Simeulue, Nanggroe Aceh Darussalam - Ambar Teguh Sulistiyani; Miladiyatu Tsania Zulfa (JDKP Jurnal Desentralisasi dan Kebijakan Publik, 2023)
Indonesia is often hit by disasters but disaster management has not been optimal. The focus of disaster management is only on post-disaster. Meanwhile, a post-disaster management approach alone will not be able to control the impact of a disaster early. This paper aims to analyze improvements in disaster mitigation for responsiveness in dealing with disasters both pre, during and post-disaster using local wisdom in the form of the "Smong" cultural heritage originating from Aceh. The research method uses descriptive qualitative. Data collection through interviews as primary data and literature study as secondary data. The research results show that disaster management is known to include pre-disaster, during disaster and post-disaster. Pre-Disaster Response Attitude as a state of mind is known in social change and community development. State of mind becomes a distinctive nuance that depicts society's social values. State of mind also informs about social changes that have occurred on a broad or narrow scale in the development system that has been experienced. Local wisdom is a form of state of mind. Local wisdom in Simelue is a continuous community learning process as communication in the face of disasters. These skills form pre-disaster response attitudes and are passed down from generation to generation. The results of the internalization of "smong" values ​​have been a blessing so that almost all residents of Simeulue Island achieved fantastic safety during the 2004 tsunami. Keywords: local wisdom, disaster management, pre-disaster response, “smong”